ESP Needs Analysis of Undergraduate Students of the Environmental Health Department - Nurhana, Riza (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2021)
Abstract: English for Specific Purposes (ESP) draws attention to a learning-centered approach in which all decisions are based on the learner’s reason for learning, hence needs analysis prior to syllabus designing of ESP program for Undergraduate Students of the Environmental Health Department is needed. This study attempts to investigate the students’ target situation and learning needs through a survey method using questionnaire and interview. The study involved 117 participants consisting of students, alumni, English teachers, content teachers and practitioners. The results indicate that speaking, reading and vocabulary are the English skills and components that should be emphasized in the teaching and learning.Abstrak: English for Specific Purposes (ESP) menekankan pada pendekatan yang berpusat pada pembelajaran dimana semua keputusan didasarkan pada alasan belajar siswa, oleh karena itu analisa kebutuhan (needs analysis) perlu dilakukan sebelum mendesain silabus program ESP bagi mahasiswa S1 jurusan Kesehatan Lingkungan. Penelitian ini bertujuan mengetahui situasi target dan kebutuhan pembelajaran para mahasiswa melalui metode survey dengan menggunakan kuesioner dan interview. Penelitian ini melibatkan 117 partisipan yang terdiri dari mahasiswa, alumni, dosen Bahasa Inggris, dosen bidang ilmu dan praktisi. Hasil penelitian menunjukkan bahwa berbicara, membaca, dan kosakata adalah keterampilan dan komponen bahasa Inggris yang harus ditekankan dalam belajar mengajar.